2020
DOI: 10.1021/acsptsci.0c00112
|View full text |Cite
|
Sign up to set email alerts
|

Identifying SARS-CoV-2 Entry Inhibitors through Drug Repurposing Screens of SARS-S and MERS-S Pseudotyped Particles

Abstract: While vaccine development will hopefully quell the global pandemic of COVID-19 caused by SARS-CoV-2, small molecule drugs that can effectively control SARS-CoV-2 infection are urgently needed. Here, inhibitors of spike (S) mediated cell entry were identified in a high throughput screen of an approved drugs library with SARS-S and MERS-S pseudotyped particle entry assays. We discovered six compounds (cepharanthine, abemaciclib, osimertinib, trimipramine, colforsin, and ingenol) to be broad spectrum inhibitors f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
130
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(137 citation statements)
references
References 42 publications
7
130
0
Order By: Relevance
“…These include cell cycle inhibitors ABE targeting Cdk4, AZ1 targeting Usp25/28, HAR targeting Dyrk1A, NIN targeting Fgfr1/2/3, and UC2 targeting p21; the endocytosis inhibitor PMZ targeting Wdr81; and the Tbk1 inhibitor AMX. Chen et al recently reported similar activity of ABE against SARS-CoV-2 (31), validating our findings. To our knowledge, the discovery that AMX, AZ1, HAR, NIN, PMZ, and UC2 possess antiviral activity against SARS-CoV-2 has not been reported.…”
Section: Discussionsupporting
confidence: 92%
“…These include cell cycle inhibitors ABE targeting Cdk4, AZ1 targeting Usp25/28, HAR targeting Dyrk1A, NIN targeting Fgfr1/2/3, and UC2 targeting p21; the endocytosis inhibitor PMZ targeting Wdr81; and the Tbk1 inhibitor AMX. Chen et al recently reported similar activity of ABE against SARS-CoV-2 (31), validating our findings. To our knowledge, the discovery that AMX, AZ1, HAR, NIN, PMZ, and UC2 possess antiviral activity against SARS-CoV-2 has not been reported.…”
Section: Discussionsupporting
confidence: 92%
“…Cepharantine was approved in Japan to treat alopecia [ 40 ], which was proposed in the last months as anti-COVID-19 therapy based on theoretical and in vitro results [ 11 ]. Our in silico results showed that cepharantine could be a potential inhibitor of furin and TPC2, being its biological action involved not only in first entry phases but also in the escape from late endosomes, a mechanism that is compatible with the results obtained in the surrogate model of viral entry here presented ( Figure 4 B) and a recently published report [ 41 ]. Moreover, in the last months, cepharantine has been identified as an experimental inhibitor of TPC2 [ 42 ].…”
Section: Discussionsupporting
confidence: 91%
“…To probe the mechanism of SARS-CoV-2 infection inhibition, we utilized the SARS-CoV-2 spike pseudotyped particle (PP) assay in HEK239T cells stably transfected with ACE2 fused to green fluorescent protein (ACE2-GFP) that are permissive to spike-mediated PP entry and transduction of luciferase. 33 All compounds inhibited PP entry, and while some toxicity was observed as measured by ATP content, the CC 50 /EC 50 ratio, or SI, indicated an efficacy independent of compound toxicity ( Figure 5 , Table 2 ). The data suggested these compounds blocked the cellular entry of SARS-CoV-2 PPs that rely on spike-mediated endocytosis and fusion in ACE2-expressing cells.…”
Section: Resultsmentioning
confidence: 95%